2019
DOI: 10.1007/s11033-019-04758-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene dosage of DAX-1, determining in sexual differentiation: duplication of DAX-1 in two sisters with gonadal dysgenesis

Abstract: Two sisters phenotypically normal females, presenting with tumor abdominal mass with histopathological findings of teratoma and gonadoblastoma associated to 46,XY male-to-female sex reversal syndrome, secondary to a duplication in DAX-1, possibly inherited of maternal gonadal mosaicism. Copy number variation and functional effects of the duplication were done by MLPA multiplex ligation-dependent probe amplification and real time PCR. DAX-1, also known as dosage sensitive sex reversal gene (DSS), is considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…According to the loop extrusion model a multiplication of NR0B1 and the insulator at CXorf21 as well as the CXorf21 and GK enhancers as present in P3, one of the duplicated CXorf21 insulators loses its function due to the lack of an opposing interaction partner, whilst NR0B1 and enhancers maintain their function with respect to the phenotype. Therefore, it is possible that this model describes a general process beyond the specific genetic rearrangements of the three patients presented here and the deletion reported by Smyk et al (2007) and would similarly apply to all previously reported Xp21.2 duplications (Barbaro et al, 2008; Barbaro et al, 2012; Barbaro et al, 2007; Dong et al, 2016; Garcia-Acero et al, 2019; Ledig et al, 2010; White et al, 2011). It is of note, that P3 also shows muscular hypotonia possibly hinting at a regulatory effect of the triplication on the expression of the DMD gene.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…According to the loop extrusion model a multiplication of NR0B1 and the insulator at CXorf21 as well as the CXorf21 and GK enhancers as present in P3, one of the duplicated CXorf21 insulators loses its function due to the lack of an opposing interaction partner, whilst NR0B1 and enhancers maintain their function with respect to the phenotype. Therefore, it is possible that this model describes a general process beyond the specific genetic rearrangements of the three patients presented here and the deletion reported by Smyk et al (2007) and would similarly apply to all previously reported Xp21.2 duplications (Barbaro et al, 2008; Barbaro et al, 2012; Barbaro et al, 2007; Dong et al, 2016; Garcia-Acero et al, 2019; Ledig et al, 2010; White et al, 2011). It is of note, that P3 also shows muscular hypotonia possibly hinting at a regulatory effect of the triplication on the expression of the DMD gene.…”
Section: Discussionsupporting
confidence: 57%
“…Among such genes is NR0B1 ( Nuclear Receptor Subfamily 0, Group B, Member 1 ; also known as DAX1 ), located within a dosage-sensitive 160kb spanning sex reversal (DSS) region at Xp21.2 (Bardoni et al, 1994). Since its first description several 46,XY GD patients with duplications including the entire NR0B1 have been reported (Figure S1, Supporting Information) (Barbaro et al, 2008; Barbaro, Cook, Lagerstedt-Robinson, & Wedell, 2012; Barbaro et al, 2007; Dong et al, 2016; Garcia-Acero et al, 2019; Ledig et al, 2010; White et al, 2011). In mice, Nr0b1 expression starts in the genital ridge of both sexes at the same time point as the expression of Sry ( sex determining region Y ), but is downregulated in the developing testis and persists in the ovary (Swain, Zanaria, Hacker, Lovell-Badge, & Camerino, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…MLPA analysis detected copy number variations in 3 patients: 2 patients, who were sisters, showed duplication of DAX1 and a 46,XY karyotype, suggesting that the causal alteration for DSDs in these patients was inherited from a parent with gonadal mosaicism; although this is a very rare characteristic, it has been previously described in a patient with DSDs, with copy number variation in another chromosomal region (27,28). In the third patient, the deletion of the SRY gene region with a 46,XY karyotype was demonstrated; in this case, the presence of SRY , as detected by FISH, suggests the probable alteration of the gene by mutation in the annealing region, which has an effect on the function of the gene, and is likely to be the cause of the DSDs phenotype (29).…”
Section: Discussionmentioning
confidence: 78%
“…(14) That phenotype has been associated with mutations, deletions, duplications, or alterations in the regulation of genes responsible for the determination of sex development and hormonal function, such as SRY, NR0B1, SOX9, NR5A1, DAX1, LHR, and AR/NR3C4, among many others. (9,10,15) From a clinical perspective, the 8 DSD 46,XY cases described herein showed conditions including hypospadias with different degrees of severity, sexual ambiguity, and a case of completely female phenotype. The SRY gene was physically present in all cases, indicating no loss, and therefore may not be involved in the presentation of DSD in those patients.…”
Section: Discussionmentioning
confidence: 90%